The Concept Of Education And Its Pedagogical Essence - Mamadjanova, Makhimir Rashidovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article presents the concept of upbringing, its importance in raising children, the stages of the formation of the upbringing process, and the directions of upbringing.